THE OBJECTIVE OF ISLAMIC BANK: A CASE STUDY IN SURAKARTA REGION - Ibrahim Fatwa Wijaya (Jurnal Keuangan dan Perbankan, 2017)
The purposes of this research were for exploring the perception of the Islamic Banking stakeholders related with the objective of Islamic Banking that operated in the dual banking system, Indonesia and for measuring the gap between the perception and expectation of the stakeholders toward the objective of Islamic bank. The primary data was collected by questionnaires. The Respondents were limited only in the Surakarta region. They were customers, lecturers, students, employees, bank managers, regulators, and ulama (Moslem religious teachers). Factor analysis was conducted for grouping or classifying the variables into the same group which had the same characters while Kruskall Wallis test was used for examining the different perception among the stakeholders. At last, paired sample t-test was used to measure the gap between perception and expectation among the stakeholders. The findings of this study were first, stakeholders concluded that social objective of Islamic was more important than the commercial one; second, there was a significant different perception on the Islamic Banking objective among the stakeholders; and third, there was a gap between the perception and expectation of the stakeholders about Islamic Banking objectives.